Occupational Health: Meeting the Challenges of the Next 20 Years - John Harrison; Leonie Dawson (Elsevier, 2016)
Background: The industrial revolution that took place in the United Kingdom (UK) between 1760 and 1830 led to profound social change. Occupational medicine was concerned with the diagnosis, treatment, and prevention of occupational diseases, that is, diseases directly caused by exposure to workplace hazards. A similar pattern of development has occurred globally. Methods: A review of relevant literature. Results: The international conceptualization and development of occupational health occurred during the 20th century. A new paradigm for occupational health has emerged that extends the classical focus on what might be termed "health risk management" that is, the focus on workplace hazards and risk to health to include the medical aspects of sickness absence and rehabilitation, the support and management of chronic noncommunicable diseases, and workplace health promotion. Conclusion: The future strategic direction for occupational health will be informed by a needs analysis and a consideration of where it should be positioned within future healthcare provision. What are the occupational health workforce implications of the vision for occupational health provision? New challenges and new ways of working will necessitate a review of the competence and capacity of the occupational health workforce, with implications for future workforce planning.